Ahlmannryggen: Maudheimvidda (Norsk Polarinstitutt, 1996)
Pages: Blad/Sheet G5S Place: Oslo
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Jutulstraumen: Maudheimvidda (Norsk Polarinstitutt, 1996)
Pages: Blad/Sheet G6S Place: Oslo
Keywords: Dronning Maud Land; geografi; kartlegging; satellite bilder

Effects of Egg Size and Parental Quality on Early Nestling Growth: An Experiment with the Antarctic Petrel - Amundsen, Trond; Lorentsen, Svein-Hakon; Tveraa, Torkild (Journal of Animal Ecology, 1996)
A large number of studies have reported a positive relationship between the egg size of birds and the subsequent growth and/or survival of nestlings, but such effects may partly be due to confounding variables, e.g. parental quality. In order to evaluate the potential effects of egg size, and of parental quality, on early nestling growth in the Antarctic petrel, we performed an experiment in which eggs of different size were swapped between nests. 2. From a sample of 300 nests with eggs of known size, we selected eggs belonging to the lower quartile (small eggs), and those belonging to the upper quartile (large eggs), with respect to volume. Half of the small eggs were exchanged with small eggs from other nests, and the other half with large eggs. A similar procedure was used for large eggs. Growth and survival of the nestlings were recorded until 12 days old. 3. Hatching success was positively related to egg size. 4. Egg size influenced nestling body mass until the age of 3 days, and tarsus length was affected until 12 days old. However, these effects were not due to an effect of egg size on growth rates, but reflected instead the influence of egg size on hatchling size. 5. In contrast to most previous studies, we found no effect of parental quality (as reflected in the size of own eggs) on foster nestling size or growth until 12 days old. This could be because egg size does not reliably reflect parental quality in the species, or because parental effects become evident only at later nestling stages. 6. We discuss why egg size variation is maintained in this and other species where egg size influences parental fitness through the survival of eggs or nestlings.
Publisher: [Wiley, British Ecological Society]
Keywords: Dronning Maud Land; fugler; ornitologi; petreller; zoologi; økologi

Geodetic measurements at Vestfjella and Heimefrontfjella - Barstad, Bjørn; Luktvasslimo, Brit Åse (Report of the Norwegian Antarctic Research Expedition 1993/94, 1996)
Keywords: Dronning Maud Land; NARE 1993/94; ekspedisjoner; geodesi; satellittbilder; topografi

A century of accumulation and temperature changes in Dronning Maud Land, Antarctica - Isaksson, Elisabeth; Karlén, Wibjörn; Gundestrup, Niels; Mayewski, Paul; Whitlow, Sallie; Twickler, Mark (Journal of Geophysical Research: Atmospheres, 1996)
Keywords: Dronning Maud Land; akkumulasjon; klima; målinger; snø; temperatur

Regulation of Food Provisioning in the Antarctic Petrel Thalassoica antarctica - Lorentsen, Svein-Håkon (Journal of Animal Ecology, 1996)
1. Life-history theory predicts that individual birds should invest in reproduction according to their current body condition and the future prospects for survival and reproduction. Thus, it could be expected that current adult body condition should significantly influence food provisioning rates, food loads and concurrent chick growth in the Antarctic petrel. 2. In order to study the significance of parental body condition I correlated meal sizes, feeding frequencies and chick growth with the body condition of the parents. 3. There was a strong correlation between the average meal size delivered to a chick and its growth rate. Adult body condition at the time of hatching was strongly correlated with the average size of meals delivered to individual chicks. Male and female body condition at the time of hatching and average body condition of the pair at the first incubation shift and at hatching significantly influenced the body mass of the chick on day 30. Male body condition and the average body condition of the pair correlated significantly with the growth rate of the chick. 4. The difference in body mass at the age of 30 days of chicks from parents with good body condition compared with chicks from parents with poorer body condition was nearly double that expected. 5. The results strongly suggest that the effort spent during the chick-rearing period, and thus reproductive success, is regulated by the body condition of the parents.
Publisher: [Wiley, British Ecological Society]
Keywords: Dronning Maud Land; NARE 1991/92; fugler; ornitologi; petreller; zoologi

Seabird research at Svarthamaren during NARE 1993/94 - Lorentsen, Svein-Håkon; Amundsen, Trond; Røv, Nils; Tveraa, Torkild (Report of the Norwegian Antarctic Research Expedition 1993/94, 1996)
Keywords: Dronning Maud Land; NARE 1993/94; fugler; ornitologi

Mass balance and dynamics on Jutulstraumen ice stream during NARE 1993/94 - Melvold, Kjetil; Hagen, Jon Ove; Laumann, Tron; Tonning, Tore (Report of the Norwegian Antarctic Research Expedition 1993/94, 1996)
Keywords: Dronning Maud Land; NARE 1993/94; glasiologi; isstrøm

Anhydrobiosis and cold tolerance in tardigrades - Sømme, Lauritz (European Journal of Entomology, 1996)
A review of the literature regarding anhydrobiosis and cold tolerance in tardigrades is presented. During increasing desiccation, invertebrates like tardigrades, rotifers, nematodes and some collembolans are able to shut down metabolism to undetectable levels. When tardigrades are entering anhydrobiosis, a tun-like structure is formed, facilitated by structural adaptations of the cuticle. Slow dehydration is essential for tun formation, and the accumulation of trehalose during this process may help to stabilize phospholipids and proteins. Wax extrusion on the cuticle surface reduces transpiration. A fraction of 5-15% of the initial body water is retained during anhydrobiosis. Tardigrades are principally aquatic organisms, but anhydrobiosis makes it possible for some species to live in habitats with changing moisture conditions. Tardigrades in anhydrobiosis may tolerate exposure to freezing temperatures of liquid gases, and some species also survive such temperatures in their hydrated state. Few investigations are available on the relation of tardigrades to temperatures more representative to their natural environments. Experimental studies, however, from Greenland and the Antarctic Continent suggest that some species overwinter both in a hydrated frozen state and in anhydrobiosis. During the summer, a number of tardigrade species have been recorded from cryoconite holes, formed on the surface of glaciers. These species are freeze tolerant since their habitats are permanently frozen during the winter.
Keywords: Antarktis; Dronning Maud Land; biomonitorering; bjørnedyr; entomologi; kuldetoleranse; polarområdene; virvelløse dyr

Glaciological measurements at Jutulgryta - Winther, Jan-Gunnar; Sand, Knut; Elvehøy, Hallgeir; Bøggild, Carl Egede (Report of the Norwegian Antarctic Research Expedition 1993/94, 1996)
Keywords: Dronning Maud Land; NARE 1993/94; glasiologi